(untitled) (Yangi O’zbekiston taraqqiyotida tadqiqotlarni o’rni va rivojlanish omillari, 2024)
In today's current times, digital technologies are rapidly entering all areas and people's lives from important topics. The development of the digital economy has become the most important task in our country. In the decision of the President of April 28, 2020 "On measures for the wide introduction of the digital economy and electronic government", by 2023 the share of the digital economy in the country's gross domestic product should be increased by 2 times, the volume of services in this field should be increased by 3 times, and their export will reach 100 million US dollars. is assigned the task of delivering to the dollar.